Does monetary policy influence the profitability of banks in New Zealand? - Vijay Kumar; Sanjeev Acharya; Ho Ly (International Journal of Financial Studies, 2020)
The study investigates the relationship between monetary policy and bank profitability in New Zealand using the generalized method of moments (GMM) estimator. Our sample comprises 19 banks from New Zealand over the period 2006-2018. Our results suggest that an increase in short-term rate leads to an increase in the profitability of banks, while an increase in long-term interest rates reduces bank profitability. In addition to monetary policy variables, capital adequacy ratio, non-performing loan ratio, and cost to income ratio are also important determinants of the profitability of banks in New Zealand. Capital adequacy ratio has a positive impact on bank profitability, while non-performing loan ratio and cost to income ratio have a negative impact on bank profitability.
Keywords: G21; G28; E58; 330; monetary policy; bank size; long-term interest rates; short-term interest rates